2002
DOI: 10.1177/088840640202500302
|View full text |Cite
|
Sign up to set email alerts
|

Unifying General and Special Education: What Does the Research Tell Us?

Abstract: The Individuals with Disabilities Education Act has provided the impetus to educate all children in more inclusive settings. With the move toward inclusion has come the recognition that changes must occur in the manner in which teachers are prepared. Since the 1970s, efforts have been made to ensure that general educators have some content in their preservice preparation programs related to disabilities either through modifying existing courses or by adding special education courses to the curriculum. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 21 publications
0
32
0
3
Order By: Relevance
“…Reports indicate that institutions of higher education in many countries have started to infuse course work about students with disabilities, and inclusion into their curriculum, yet evidence suggests that a single course may not be effective (i.e., Staton and McCollum 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Reports indicate that institutions of higher education in many countries have started to infuse course work about students with disabilities, and inclusion into their curriculum, yet evidence suggests that a single course may not be effective (i.e., Staton and McCollum 2002).…”
Section: Discussionmentioning
confidence: 98%
“…These results are preliminary but suggest that models of inclusive teacher education such as the one described herein may warrant further investigation (Welch, 1996). This is particularly true, given the lack of research to date on the outcomes of unified teacher education programs (Stayton & McCollum, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…In regard to effectively preparing teachers to work confidently and competently in inclusive settings with young children with diverse abilities, it has been recommended that general education and special education programs be integrated (Miller, 1992;Bredekamp, 1992, as cited in Stayton & McCollum, 2002). It has been suggested that successful inclusion of young children with disabilities cannot be achieved as long as personnel preparation is segregated.…”
Section: Recommendations For Changementioning
confidence: 97%